Perovskite-like ceramic hole transport material for quantum dot sensitized solar cells. (August 2021) - Akhil, S.; Kusuma, J.; Akash, S.; Geetha Balakrishna, R.
Graphical abstract: Highlights: Low cost, easily processable and high mobility solid state electrolyte for QDSSCs. Perovskite like ceramic acts as passivation layer to supress electron recombination enabling high Voc . Ceramic hole transport layer with high hole mobility, low cost and easy processable for QDSSC. Abstract: Considering the minus points of Polysulfide redox electrolyte we explored Lanthanum Strontium Manganite to see the possibility of its usage in Quantum dot sensitized solar cells (QDSSCs) as electrolyte. Variations in material morphology synthesized via different methods and its effect on device performance and charge transfer dynamics across counter electrode are studied. The ceramic acts as a good passivation layer reducing the back transfer of electrons resulting in greater Voc and higher stability of cells. This study opens scope for use of such ceramics to completely replace the liquid electrolyte.